Christ and Culture: A Belated Assessment of H.R. Niebuhr for Preaching (Homiletic, 2017)
H. Richard Niebuhr’s Christ and Culture (1951) has had enduring scholarly appeal, yet its impact on preaching is unclear. His types can be adapted to represent a range of listener perspectives on controversial issues, or to form categories with which to assess cultural engagement in sermons. Nonetheless, cultural attitudes have changed since Niebuhr’s time, and scholarly critiques of his project are instructive in themselves, they can help preachers to be more sensitive in dealing with cultural issues. These shifts in attitude may limit the value of his types, at least without an additional type to better address listeners’ needs.